2022
DOI: 10.1093/jac/dkac036
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline population pharmacokinetics in critically ill patients with decompensated cirrhosis and severe infections

Abstract: Objectives Physiopathological changes in advanced cirrhosis could alter tigecycline pharmacokinetics (PK), thus affecting serum drug concentrations and compromising target attainment. We aimed to describe tigecycline PK in patients with decompensated cirrhosis and severe bacterial infections, identify the sources of PK variability and assess the performance of different dosing regimens to optimize the PK/pharmacodynamic (PD) target. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“… 24 Besides, in Bastida’s study, the dosage of tigecycline administration was not provided. 25 The time of samples collection in patients in these eight studies varied widely, for example, in Broeker’s study, arterial blood samples were collected as follows: 0 (before the start of infusion), after the end of infusion (1, 1.25, 1.5, 1.75, 2, 4, 6, 8, and 12 h), while Zhou et al reported that the blood samples were obtained before the ninth dose of tigecycline and at 0, 3, and 8 h after the end of infusion. 18 , 23 To quantify tigecycline concentrations in these samples, the high-performance liquid chromatography and liquid chromatography method with tandem mass spectrometer detection systems were used in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 24 Besides, in Bastida’s study, the dosage of tigecycline administration was not provided. 25 The time of samples collection in patients in these eight studies varied widely, for example, in Broeker’s study, arterial blood samples were collected as follows: 0 (before the start of infusion), after the end of infusion (1, 1.25, 1.5, 1.75, 2, 4, 6, 8, and 12 h), while Zhou et al reported that the blood samples were obtained before the ninth dose of tigecycline and at 0, 3, and 8 h after the end of infusion. 18 , 23 To quantify tigecycline concentrations in these samples, the high-performance liquid chromatography and liquid chromatography method with tandem mass spectrometer detection systems were used in these studies.…”
Section: Resultsmentioning
confidence: 99%
“… A two-dimensional liquid chromatographic system, which contains two parts: the first separation system (LC1) and second separation system (LC2). 35 ng/mL Bastida et al 25 Prospective NR 30 min before drug administration (pre-dose), and 1, 2, 5 and 8–12 h after drug administration Liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) method 10 ng/mL Abbreviations : NR, not reported; LLQ, lower limit of quantifcation. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was surprising that only a few PK/PD models were available for OMC. A glance at the other third-generation tetracyclines shows that, for tigecycline, for example, only a few PK/PD modelling studies have been published to date [ 96 , 97 , 98 ]. As adjusted doses of tigecycline have been suggested for patients with severe hepatic functions [ 98 ], the only factor found in PK models for OMC affecting PK was the timing of food consumption.…”
Section: The Case Of Omadacycline: Pk/pd Modelling Data Still Scarcementioning
confidence: 99%
“…In critically ill patients, pathophysiological changes may affect drug PK, thus affecting the required dose ( Blot et al, 2014 ; Borsuk-De Moor et al, 2018 ; Broeker et al, 2018 ). PK changes in patients with severe illness include changes in the clearance (CL) rate caused by increased cardiac output or organ failure, and changes in distribution volume (Vd) caused by increased vascular permeability or changes in protein binding ( Bastida et al, 2022 ). The status of patients will change according to disease development.…”
Section: Introductionmentioning
confidence: 99%